Internal locus of control and financial well-being among university students / Wan Rasyidah Wan Nawang ... [et al.] - Wan Nawang, Wan Rasyidah; Kamarudin, Ume Maisarah; Anwar, Intan Fatimah; Hashim, Nor Haziah (Universiti Teknologi MARA Selangor, 2024)
This study delves into the factors influencing financial well-being among Malaysian university students, addressing the rising debt concerns among young adults under 30. This study is grounded in the Social Cognitive Theory (SCT). Data were gathered from 299 university students through a self-administered survey, which was subsequently analyzed with Partial Least Square – Structural Equation Modelling. The findings indicate that an internal locus of control significantly influences financial attitude, financial behavior, and financial confidence. Notably, financial behavior and financial confidence are crucial predictors of financial well-being, while financial attitude was found to be insignificant. Additionally, financial behavior and financial confidence mediate the relationship between internal locus of control and financial well-being, whereas financial attitude does not serve as a mediator. The results suggest that individuals with a strong internal locus of control are more likely to exhibit positive financial behaviors and greater financial confidence, ultimately enhancing their financial well-being. This study strengthens the SCT model and contributes new dimensions to the literature by examining financial attitude, financial behavior, and financial confidence as mediating factors influencing university students' financial well-being. The results also provide policymakers and relevant agencies with useful information on how to further improve university curricula and foster sound financial practices to raise the financial well-being of university students.